2008
DOI: 10.1029/2008gl033466
|View full text |Cite
|
Sign up to set email alerts
|

Local wind system in the Rongbuk Valley on the northern slope of Mt. Everest

Abstract: To better understand the local wind systems in the Himalayas, wind and related atmospheric parameters were observed in the Rongbuk Valley on the northern slope of Mt. Everest, during the HEST2006 campaign, from May 29 to June 29, 2006. Data analysis and a simple numerical simulation show that the dominating down‐valley flow in this valley is mainly formed by the thermally driven winds, “valley wind”, “mountain wind” and “glacier wind”. The vertical air motion is composed of a descending flow from the morning t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 9 publications
4
46
0
Order By: Relevance
“…At 10:00, the ratio of the down valley wind increased with increasing wind speed. This is further evidence that the strong down-valley flow induced by (normal) glacier wind prevailed during the daytime, which is consistent with the results of Zou et al (2008). Therefore, from 12:00, the strong down-valley flow induced by (normal) glacier wind influences the turbulent spectrum.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…At 10:00, the ratio of the down valley wind increased with increasing wind speed. This is further evidence that the strong down-valley flow induced by (normal) glacier wind prevailed during the daytime, which is consistent with the results of Zou et al (2008). Therefore, from 12:00, the strong down-valley flow induced by (normal) glacier wind influences the turbulent spectrum.…”
Section: Resultssupporting
confidence: 80%
“…According to the former studies of glacier wind (Shen and Gao 1975;Jiro 1987, Ludecke and Kuhle 1991, and Zou et al 2008, spectra and co-spectra were analyzed depending on the prevailing wind; case A-southerly wind speed larger than 6 m s À1 during daytime, case B-southerly with wind speed less than 6 m s À1 and case Cnortherly wind. In Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…0.75 between the daily variations of the net radiation flux and the down-valley surface wind. These results support the thermally driving mechanism of surface wind in mountain regions [Whiteman, 1990;Egger et al, 2000;Zou et al, 2007].…”
Section: Surface Windssupporting
confidence: 70%
“…Everest for investigating the Himalayan circulation system. Preliminary studies based on the observation data showed that the surface wind system in the Rongbuk Valley is composed of various thermally driven mountain circulations [Zou et al, 2007].…”
Section: Introductionmentioning
confidence: 99%